The Justification of Rights Violations: Section 1 of the Charter - Panaccio, Charles-Maxime (The Oxford Handbook of the Canadian Constitution, 2017)
This chapter is about the interpretation of section 1 of the Canadian Charter of Rights and Freedoms. Section 1 allows ‘limits’ to constitutional rights insofar as they are reasonable and justified in a free and democratic society. It asks the state for moral justification when a right has been infringed by state action. Moral justification has formal and substantive aspects; therefore the application of section 1 deploys a formal framework of proportionality nestled within a thin conception of liberal democratic political morality. The chapter also addresses the relative moral importance of the notion of ‘rights’, as well as the relevance of institutional considerations. It concludes that the section 1 framework follows a standard model of moral justification and cannot be significantly improved upon.